Compression and energy absorption properties of the truss-like lightweight materials based on symmetric groups. (1st January 2023) - Ma, Zhenhao; Ma, Wensuo; Ma, Zhenyu; Huang, Zhaohua; Yang, Liguang; Xu, Yonghao
Abstract: Truss-like lightweight materials (TLMs) have been widely used in aeronautics and astronautics, because of excellent mechanical property and superior energy absorption capability. The design of TLMs' meso-structures was a critical task to improve its performance. Hence, a structure design method based on the symmetric groups was proposed for TLMs, and a novel hexagonal prism TLM's meso-structure was deduced by the symmetric and translational operations of the space group P 6 mm . To investigate the performance of the novel TLM, the mechanical analysis model was established. The predictive equations of compression performance was proposed based on Euler–Bernoulli beam theory. The stress distribution of the novel TLM's meso-structure under compression load was discussed by the finite element analysis method, and its compression and energy absorption properties were investigated. The simulation results were in agreement with the predictive results. In addition, the common FCC and BCC TLMs were discussed using the symmetry group analysis method, and their compression properties were predicted. The results showed that the proposed novel TLM in this study had better compression property than BCC and FCC TLMs at the same relative density.